A Characterization of Weak $n$-Tilting Modules (Journal of Mathematical Study, 2024)
It is well known that weak $n$-tilting modules are vital in tilting theory, whichare generalizations of $n$-tilting and $n$-cotilting modules. The aim of this paper is to givea new characterization of weak $n$-tilting modules. In order to do that, we introducethe notion of weak $n$-star modules. We study more deeply the properties of them.Moreover, connections between (co) star and weak $n$-star modules are given.